Complex aesthetic treatment on anterior maxillary teeth with malposition - Febriastuti Febriastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Complex aesthetic treatment on anterior teeth involves more than one caries tooth with malformed shape and malposition. Purpose: The purpose of this paper is to find the alternative treatment for anterior maxillary teeth with malposition. Case: In this case, a 25 year-old man with a peg shaped teeth and caries on several teeth and malposition can be treated with complex aesthetic treatment. Case management: Endodontic pulpectomy treatment on anterior maxillary teeth and post construction with splint porcelain fused to metal crowns on 11, 12, and 21, 22 to correct the shape and position into normal position. Conclusion: Malformed and malpositioned teeth with caries can be treated with complex aesthetic treatment.